Experimental Research on the Regeneration of Incomplete Crystallographic KH2PO4 Crystal Enclosed by Singular Face. Issue 8 (12th June 2019) - Wang, Pengfei; Li, Mingwei; Xiao, Linhai
Abstract: The phenomenon of thin surface layer growth during the regeneration of incomplete crystallographic potassium dihydrogen phosphate crystal has not been thoroughly elucidated to date. In the present study, four sets of incomplete crystallographic KH2 PO4 crystals enclosed by singular faces are designed to observe their regeneration characteristics in supersaturated solution. In all the crystals, even though every crystal face is singular surface, thin surface layers still grow from crystal edges or concave angles to repair themselves to convex polyhedrons. Through surface energy calculation, it is found that the thin surface layer growth encounters higher growth barrier than ordinary layer‐by‐layer growth. Here, an assumption is proposed that the incomplete crystal possesses a "potential of morphology repair", which drives the thin surface layers growing to repair itself into complete form. This assumption is confirmed to some extent by a thin surface layer fragments experiment. The experiment implies that thin surface layer is the same as the ordinary crystal seed once separated from incomplete crystal, and its growth rate is one order slower than in incomplete crystal. Abstract : Compared with layer‐by‐layer growth, thin surface layer growth encounters a larger growth barrier to a metastable state of larger energy. It is a dynamic and thermodynamically unfavorable growth mode and can never be a spontaneous process. It is assumed that the incomplete crystal possesses a "potential of morphology repair, " which drives thin surface layers growing and make the regeneration happen.